Pengaruh Faktor Sosial Terhadap Minat Menggunakan Layanan Keuangan Syariah - Hilman Fauzi Harahap; Marliyah Marliyah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The influence of social factors on interest in using Islamic financial services is an important topic in the banking industry. Social factors such as reference groups, family, role, and status have a significant influence on purchasing decisions at Islamic banks. This study uses qualitative research methods to understand the social dynamics that influence people's interest in using Islamic financial services. The results show that social factors, including social environment and Islamic financial literacy, influence people's interest in using Islamic financial services. Therefore, Islamic banks need to pay attention to social factors in designing marketing strategies and services in order to meet the needs and desires of the community. The suggestion is to conduct market research to identify the needs and preferences of the community regarding Islamic financial products and services.